Proposed Marketing Strategies To Achieved Target For The Indonesian Creator Economy - Reyhan, Achmad; Fachira, Ira (Kompetensi (Competence : Journal of Management Studies), 2023)
Micro, Small, and medium enterprises (MSMEs) are businesses that have the ability to develop and contribute to the country's economy. The number of MSMEs in Indonesia continues to increase and the government continues to push to join the digital ecosystem. Indonesia Creator Economy (ICE) is an influencer management in Indonesia. ICE aims at providing accurate, engaging and informative digital media content. This study uses a case study model with qualitative descriptive method, and the data collection used is observation, interviews, documentation. As a result of FDG (Focus Group Discussion), This new business model canvas was developed based on fish bones and equipped with supporting data obtained from FDG. Based on the fishbone, the cause of low target achievement is caused by ICE's lack of understanding of the segment and target market. Related identification and analysis of strategy on ICE is done through the application of nine elements on the business model canvas include ; customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. So the strategy implemented by ICE is to increase awareness on marketing aspects with several programs and increase workforce.